1997
DOI: 10.1002/(sici)1097-0142(19970401)79:7<1438::aid-cncr22>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy 7 myelodysplastic syndrome and other second malignant neoplasms in children with neurofibromatosis type 1

Abstract: Children with NF1 are susceptible to the development of malignant myeloid disorders both as a primary event and as an SMN. Additional molecular genetic analysis is necessary to determine if the NF1 gene is inactivated by somatic mutation in these secondary leukemias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 0 publications
0
52
0
Order By: Relevance
“…Children with neurofibromatosis type 1 are at increased risk of developing both primary and treatment-related malignancies, including t-MDS/t-AML. 16,17 Indeed, treatment of Nf1 knockout mice with radiotherapy and alkylating agents lead to a significant increase in myeloid neoplasms. 18,19 We recently described germline mutations in the C-RAF proto-oncogene that might predispose their carriers to the primary tumor, as well as to t-AML.…”
Section: Loss Of Rkip In T-aml a Zebisch Et Almentioning
confidence: 99%
“…Children with neurofibromatosis type 1 are at increased risk of developing both primary and treatment-related malignancies, including t-MDS/t-AML. 16,17 Indeed, treatment of Nf1 knockout mice with radiotherapy and alkylating agents lead to a significant increase in myeloid neoplasms. 18,19 We recently described germline mutations in the C-RAF proto-oncogene that might predispose their carriers to the primary tumor, as well as to t-AML.…”
Section: Loss Of Rkip In T-aml a Zebisch Et Almentioning
confidence: 99%
“…This is particularly relevant in persons with NF1 as retrospective clinical data suggest that treatment with genotoxins for a primary cancer markedly ncreases the risk of common SMNs such as myeloid leukemia and soft tissue sarcoma (29,30) Based on these clinical observations and on the lack of robust animal models of SMN, the Shannon lab administered either the alkylating agent cyclophosphamide (CY), a single dose of total body irradiation (TBI), or both genotoxins to heterozygous Nf1 mutant mice (Nf1 +/-) (7, 9). When delivered alone or in combination with cyclophosphamide, TBI induced a spectrum of SMNs in Nf1 +/-mice that included myeloid malignancies, soft tissue sarcomas, and breast carcinomas.…”
Section: G12dmentioning
confidence: 99%
“…Neurofibromatosis type 1 (NF1) is an autosomal, dominant Review ª 2007 The Authors disorder in which NF1 mutations result in deregulated RAS signalling. Children with NF1 have been shown to be susceptible to the development of secondary malignant myeloid disorders following genotoxic treatment (Maris et al, 1997). In addition, Mahgoub et al (1999) demonstrated that heterozygote NF1 knockout mice were susceptible to t-AML following treatment with alkylating agents.…”
Section: Genetic Mutations Predisposing To T-amlmentioning
confidence: 99%